Struggling to Fix Teams in Real Work Settings: A Challenge Assessment and an Intervention Toolbox. (8th April 2021) - Alcover, Carlos-María; Rico, Ramón; West, Michael
Abstract: After more than 80 years in predicting organizational performance, empirical evidence reveals a science of teams that seems unable to consistently implement solutions for teams performing in real work settings –outside and away from the isolated teams breeding in research laboratories in the academic context. To bridge this growing practitioners-researchers divide, we first identify five main challenges involved in working with teams today (purposeful team staffing; proper task design and allocation; task and interaction process functionality; appropriate affective tone; and suitable team assessment). And second, we offer a toolbox of interventions (empowering and restorative) to help practitioners to transform the potential threats inherent in these challenges into opportunities for team effectiveness. Our five-challenge diagnosis and proposed intervention toolbox contribute to better address research questions and theoretical falsifiability using teams performing in real work settings, and to assess and intervene in teams by adjusting their internal functioning to contextual conditions and constraints.